#TITLE_ALTERNATIVE# - ADI PUTRA (NIM : 12214035), ANDREAS
Integrated capacitance-resistive model (ICRM) is developed as a new rapid method based on material balance to evaluate the performance of a reservoir, by generalizing many of its uncertainties into unknown parameters (t and f) that could be solved by only using cumulative injection and production of a particular or many wells at once. Since ICRM only models the cumulative liquid production on a production well, an oil fractional model needed to be used for modelling the cumulative oil production for the complete analysis of the reservoir performance. In this study, Gentil oil fractional-flow model is used to model the oil fraction for its simplicity of the data required. ICRM and Gentil oil fractional-flow model can be utilized in many well configurations, including different types of injection well patterns. Each pattern will have different behavior to solving both ICRM and fractional oil model parameters. This study focuses on effects of different types of regular injection well pattern to ICRM and Gentil oil fractional-flow modelÃ‚Â’s parameters. The types of pattern identified in this study are inverted spot pattern, normal spot pattern, direct line pattern and staggered line pattern. The study also identifies the effect of irregular injection well pattern of the mentioned types to the parameters. Irregular patterns affect different behavior to each parameter due to varied angles and distances formed by each of producer and injector well. Result of the study shows that both regular and irregular pattern has different effect to each parameter, as well as the effect of various angle and distance to each parameter varies dependent to the observed parameter itself.